2006
DOI: 10.1166/jnn.2006.428
|View full text |Cite
|
Sign up to set email alerts
|

Nanospheres of a Bisphosphonate Attenuate Intimal Hyperplasia

Abstract: The present study explored a novel strategy for attenuation of restenosis after arterial injury by a bisphosphonate encapsulated in polymeric nanoparticles (NP) for transient selective depletion of macrophages. A bisphosphonate (BP), 2-(2-Aminopyrimidino) ethyldiene-1,1-bisphosphonic acid betaine (ISA), was successfully formulated in 400 nm sized polylactide/glycolide-based NP with high yield (69%) and entrapment efficiency (60% w/w). ISA NP, but not blank NP or free ISA, exhibited specific and significant cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 0 publications
2
29
0
Order By: Relevance
“…Long term inactivation of macrophages carries the danger of immunosuppression and infection. However, as in several studies in rabbits and rats, no overt infection was observed with partial and transient monocytes depletion (12)(13)(14)(15)(16)42,46,59).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Long term inactivation of macrophages carries the danger of immunosuppression and infection. However, as in several studies in rabbits and rats, no overt infection was observed with partial and transient monocytes depletion (12)(13)(14)(15)(16)42,46,59).…”
Section: Discussionsupporting
confidence: 75%
“…Circulating blood monocytes fully recovered 7 days after injection. The effects of liposomal simvastatin are limited to cells with phagocytic capacity with no effect on other cells, such as SMC or endothelial cells, as has been demonstrated in animals treated with liposomal BPs (12)(13)(14)(15)(16)42,46). Simvastatin leaking from inactivated monocytes and the delivery system would accumulate mainly in the liver.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Previously, Afergan et al and Cohen-Sela et al reported that RAW264.7 cells exposed to nanoparticles, including liposomes, were transiently inactivated, thereby compromising the function of cultured macrophages and leading to a diminished inflammatory response. 35,36 Overall, our results suggest that PA-LIP and CL-LIP could potentially be used in vivo without triggering a negative response in endothelial cells or macrophages, but this needs further confirmation.…”
Section: Discussionmentioning
confidence: 76%